CAFGU ; Fr. Hontiveros ; Cebu [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1989)
Takes a look on CAFGU, a civilian group but armed and trained interview with Fr. Ed. Hontiveros, a composer of Sunday Mass songs; and the urbanization and economic boom in Cebu.
CAFGU (16 min.) -- Fr. Hontiveros (12 min.) -- Cebu (8 min.)
VHS.
Keywords: Citizens Armed Forces Geographical Units; Hontiveros, Ed -- Interviews; Cebu -- Description and travel; Cebu -- Economic conditions -- 1988.